ADAMTS-13-regulated nuclear factor E2-related factor 2 signaling inhibits ferroptosis to ameliorate cisplatin-induced acute kidney injuy: Running title: Role of ADAMTS-13 and ferroptosis in AKI. Issue 2 (20th December 2021) - Meng, Xiaoyan; Huang, Wenjing; Mo, Weiwei; Shu, Tingting; Yang, Haoqiang; Ning, Haibo
ABSTRACT: ADAMTS-13 plays an important role in acute kidney injury (AKI), but the mechanism of cisplatin (CP) induced AKI remains unclear. Ferroptosis is increased in CP-induced AKI, and ADAMTS13 levels are associated with ferritin expression. In this article, we will explore the relationship between the three. After CP induction, mice were given 0.1 and 0.3 nmol/kg ADAMTS-13, and then serum creatinine (Scr) and blood urea nitrogen (BUN) were detected by the kits. The pathological changes of renal tissue were observed by staining with HE and PAS staining, and Western blot detected the expressions of KIM1 and NGAL in renal tissu. Perl's staining detected iron deposition in renal tissues, the kits detected iron levels, and western blot detected the expression of ferroptosis related proteins. Then the mechanism was further explored by adding ferroptosis inhibitors Ferrostatin 1 (Fer-1) and iron supplements Fe. The expression of Nrf2 pathway related proteins were detected by Western blot. We found that ADAMTS13 alleviated CP-induced ferroptosis in AKI mice with renal function impairment and tubular damage. Fer-1partially reversed CP-induced AKI, and Fe exacerbated this effect. ADAMTS13 alleviated CP-induced inflammatory response and oxidative stress in AKI mice, during which the Nrf2 signaling pathway was abnormal. Overall, ADAMTS-13-regulated Nrf2 signaling inhibits ferroptosis to ameliorate CP-induced AKI.